Comparative Genomics of Thalassobius Including the Description of Thalassobius activus sp. nov., and Thalassobius autumnalis sp. nov. - Pujalte, María J.; Lucena, Teresa; Rodrigo-Torres, Lidia; Arahal, David R. (Frontiers in Microbiology, 2018)
A taxogenomic study was conducted to describe two new Thalassobius species and to analyze the internal consistency of the genus Thalassobius along with Shimia and Thalassococcus. Strains CECT 5113T, CECT 5114, CECT 5118T and CECT 5120 were isolated from coastal Mediterranean seawater, Spain. Cells were Gram-negative, non- motile coccobacilli, aerobic chemoorganotrophs, with an optimum temperature of 26ºC and salinity of 3.5-5%. Major cellular fatty acids of strains CECT 5113T and CECT 5114 were C18:1 7c/6c and C10:0 3OH, G+C content was 54.4-54.5 mol% and were able to utilize propionate, L-threonine, L- arginine and L-aspartate as carbon sources. They exhibited 98.3% 16S rRNA gene sequence similarity, 75.0-75.1 ANIb and 19.5-20.9 in silico DDH to type strain of their closest species, Thalassobius maritimus. Based on these data, strains CECT 5113T and CECT 5114 are recognized as a new species, for which the name Thalassobius activus is proposed, with strain CECT 5113T (=LMG 29900T) as type strain. Strains CECT 5118T and CECT 5120 were found to constitute another new species, with major cellular fatty acids C18:1 7c/6c and C18:1 7c 11-methyl and a G+C content of 59.8 mol%; they were not able to utilize propionate, L-threonine, L- arginine or L-aspartate. Their closest species was Thalassobius mediterraneus, with values of 99.6% 16S rRNA gene sequence similarity, 79.1% ANIb and 23.2% in silico DDH compared to the type strain, CECT 5383T. The name Thalassobius autumnalis is proposed for this second new species, with strain CECT 5118T (=LMG 29904T) as type strain. To better determine the phylogenetic relationship of the two new species, we submitted twelve genomes representing species of Thalassobius, Shimia and Thalassoccocus, to a phylogenomic analysis based on 54 single protein-encoding genes (BCG54). The resulting phylogenomic tree did not agree with the current genera classification, as Thalassobius was divided in three clades, Thalassobius sensu stricto (T. mediterraneus, T. autumnalis sp. nov. and T. gelatinovorus), Thalassobius aestuarii plus the three Shimia spp (S. marina, S. haliotis and Shimia sp. SK013) and finally, Thalasobius maritimus plus T. activus sp. nov. Thalassococcus halodurans remained apart from the two genera. Phenotypic inferences from explored genomes are presented.